Mid-grip forces and moments estimated from pole deformation in pole vaulting - Uematsu, R.; Koike, S. (ISBS Proceedings Archive (Michigan), 2018)
The pupose of this study was to propose a method which estimates the resultant force and moment from the shape of a deformed pole based on a quasi-static equilibrium equation. The force and moment were assumed to be exerted, at the middle point of both hands, on the pole. The pole was modelled as a series of 11 rigid segments connected to the adjacent segment via a virtual rotational joint with a rotational spring component. The stiffness of the spring was identified from a static load test. The resultant mid-grip force and moment were calculated from a static force-moment equilibrium equation. The results indicate that the kinetic values obtained by the proposed method show similar values reported in a previous study which utilized a force plate.